THE IMPACT OF CUSTOMER RELATIONSHIP MANAGEMENT ON THE FINANCIAL PERFORMANCE OF SERVICE ORGANIZATIONS: A STUDY ON A SAMPLE OF SERVICE ORGANIZATIONS IN BAGHDAD CITY - Hameed Shukur AbdulAmeer Al-Azzawi; Aymen Hadi Talib (Scholars Digest Publishing, 2025)
The research addresses a vital and significant topic for critical institutions in general, and service institutions in particular. It examines the role of customer relationship management (CRM) in the financial performance of service institutions by surveying the opinions of several managers from various service institutions in Iraq. The study aims to identify the key requirements for CRM in enhancing the financial performance of service institutions. A questionnaire was distributed to 110 managers in some service institutions in Baghdad, of which 89 valid responses were collected for analysis. The SPSS program was utilized to analyze the questionnaire results. The study concluded that there is a relationship and impact of CRM on the financial performance of service institutions, highlighting the fundamental role of CRM in the financial performance of the studied service institutions. The study proposed several suggestions, including the need for better investment in CRM programs and their continuous updating to keep pace with advancements. The study results show that the questionnaire has high reliability and validity, with a Cronbach's alpha of 0.864 and a self-validity coefficient of 0.93. A significant correlation was found between customer knowledge and performance dimensions, with correlation coefficients of 0.295 for sales, 0.457 for market share, and 0.374 for profitability. Regression analysis revealed that customer knowledge positively impacts performance, with a coefficient of 0.363. On a more specific level, customer knowledge significantly influences sales (0.304), market share (0.209), and profitability (0.140).
Keywords: Customer Relationship Management, Financial Performance.